SYNTHESIS OF THE OPTIMAL OBSERVING FILTER B NAVIGATION SYSTEM - Glazunov , I. E.; Bilak, N. V.; Vovk , V.G.; Litvinova , O. V. (Problems of Informatization and Management, 2021)
The paper presents the algorithm and the results of the selection of the optimal structure of the filter-observer of the output state of the actually existing meter of the ship's course. In the course of synthesis the necessary navigational information received by results of dynamic certification of the investigated system of measurements is used.